The method of deriving human T-cell clones alters the proportion of IL-10-producing cells. - Cohen, S; Webb, L; Feldmann, M (1996)
It is now well documented that the mode of primary stimulation in the mouse determines the ratio of Th1-, Th0- or Th2-type T cells obtained. In this paper we determine whether driving and cloning human peripheral blood mononuclear cells (PBMC) non-specifically with interleukin-2 (IL-2) and/or IL-4 and mitogen, will differentially select T cells for IL-10 production. The presence of IL-2 during culture (with or without IL-4) yielded predominantly Th1-type clones (81% of clones with IL-2 alone and 77% with IL-2 + IL-4) and a low frequency of Th0-type clones (19% of clones with IL-2 and 10% of clones with IL-2 + IL-4), whereas IL-4 alone increased the yield of the IL-4 producing Th0 (35%) clones. The proportions of IL-2-producing clones did not alter with treatment; however, the combination of IL-2 + IL-4 altered the proportions of IL-10-producing clones. 47% of IL-2-cultured cells and 51% of IL-4-cultured cells produced IL-10 respectively, whereas only 22% of clones driven with IL-2 + IL-4 produced detectable levels of IL-10. Thus in the preliminary experiments described here we have demonstrated that the cytokines used to initially drive out human T cells and maintain the T-cell growth can skew the Th1/Th2/Th0 cytokine profiles of the clones obtained from mitogen-stimulated cultures. Moreover and unexpectedly the proportion of IL-10-producing cells is altered. These results are important in interpreting analysis of the cytokine profiles of human T cells and raise questions concerning how we should derive T-cell clones for a cytokine analysis that truly reflects the in vivo situation.